A qualitative content analysis of retained surgical items: learning from root cause analysis investigations. (30th March 2020) - Hibbert, Peter D; Thomas, Matthew J W; Deakin, Anita; Runciman, William B; Carson-Stevens, Andrew; Braithwaite, Jeffrey
Abstract: Objective: To describe incidents of retained surgical items, including their characteristics and the circumstances in which they occur. Design: A qualitative content analysis of root cause analysis investigation reports. Setting: Public health services in Victoria, Australia, 2010–2015. Participants: Incidents of retained surgical items as described by 31 root cause analysis investigation reports. Main Outcome Measure(s): The type of retained surgical item, the length of time between the item being retained and detected and qualitative descriptors of the contributing factors and the circumstances in which the retained surgical items occurred. Results: Surgical packs, drain tubes and vascular devices comprised 68% (21/31) of the retained surgical items. Nearly one-quarter of the retained surgical items were detected either immediately in the post-operative period or on the day of the procedure (7/31). However, about one-sixth (5/31) were only detected after 6 months, with the longest period being 18 months. Contributing factors included complex or multistage surgery; the use of packs not specific to the purpose of the surgery; and design features of the surgical items. Conclusion: Retained drains occurred in the post-operative phase where surgical counts are not applicable and clinician situational awareness may not be as great. Root cause analysis investigation reports can be a valuable means of characterizing infrequently occurring adverse events such as retained surgical items. They may detect incidents that are not detected by other data collections and can inform the design enhancements and development of technologies to reduce the impact of retained surgical items.